The effects of elevated carbon dioxide on the secondary metabolites and biological activities in Moringa oleifera Lam. and Moringa peregrina Forssk - Moloi, Thato (University of the Witwatersrand, Johannesburg, 2023)
Climate is crucial for the distribution and survival of medicinal plants as it can influence phytochemicals and regulatory hormones that are responsible for the normal growth and development, as well as their interactions with the environment. Thus, it is important to understand how climate change will impact these crucial plant compounds and hormones that play a significant role in the plant’s survival and development. With the increasing CO2 in the atmosphere, it is expected that climate change effects will be devastating to the world and Southern Africa. The present study intended to achieve two aims, the first being to investigate the impacts of elevated CO2 (eCO2) on the secondary metabolites and biological activities of two important Moringa species, Moringa oleifera Lam. (M. oleifera) and Moringa peregrina - (Forssk.) Fiori (M. peregrina). The second aim was to investigate how the use of M. oleifera leaf extract (MLE) based and commercial (PhytoStim®) biostimulants influence the productivity as well as the adaptability of M. oleifera and M. peregrina under elevated eCO2. The first set of three-month-old potted plant samples were exposed to 400 ppm (control), 600 ppm and 800 ppm for three months, respectively. The second set of plants were placed in the greenhouse and sprayed (foliar application) with 200 mL of M. oleifera leaf extract (MLE) and 200 mL commercial biostimulant PhytoStim® every second week for three months, respectively. The control samples were unsprayed. The third set of plants were exposed 600 ppm and 800 ppm (separately) and simultaneously sprayed with 200 mL of M oleifera leaf extract (MLE) and 200 mL commercial PhytoStim® (separately) every second week for three months to assess the influence of biostimulants on the adaptability of the Moringa species under eCO2. The control samples under 400 ppm were unsprayed. In this study, 80% methanolic extracts from all the above mentioned treatments of M. oleifera and M. peregrina were screened for 17 secondary metabolite groups (tannins, saponins, flavonoids, quinones, phenols, terpenoids, cardiac glycosides, coumarins, steroids, phlobatannins, anthracyanine, volatile oils, phytosterols, triterpenoids, proteins and amino acid, glycosides, carbohydrates) using qualitative methods. Quantitative analyses were performed to determine the total phenolic content (TPC), total flavonoid content (TFC), total tannin content (TTC) and total proanthocyanidin content (TPAC). The antioxidant assays were performed to determine the reducing, scavenging and chelating abilities against DPPH, H2O2 and metal (Iron) chelating. The antimicrobial activities against gram negative Escherichia coli and gram-positive Staphylococcus aureus, Streptomyces albulus were assessed by using the agar well diffusion assay. In the control samples, out of 17 screened secondary metabolites, four (phytosterols, volatile oils, anthocyanin and phlobatannins) were not detected in both species’ extracts. On average, M. peregrina showed higher total content of tannins, phenolics, flavonoids and proanthocyanidins. M. peregrina showed stronger antioxidant activity against iron chelating and H2O2, whilst M. oleifera showed stronger antioxidant activity against DPPH. Both M. oleifera and M. peregrina extracts displayed an acceptable bacterial growth inhibition capability (ZOI ≥10 mm) with only S. albulus being resistant to the control of M. oleifera. Qualitative phytochemical analysis indicated the presence of secondary metabolites such as tannins, saponins, flavonoids under 600 ppm and a slight decline under 800 ppm in both species. The quantitative analysis indicated an increase in the total content of phenols, flavonoids (flavanols), tannins, and proanthocyanidins. An increase in CO2 resulted in an increase in the activity of antioxidants and antibacterial for both species. On average, Moringa peregrina showed higher accumulation of secondary metabolites, higher antioxidant and antibacterial activities in comparison to Moringa oleifera. The foliar application of MLE and PhytoStim® showed an increase in some secondary metabolites and decrease in metabolites such as tannins and phenols in M. oleifera. The application of biostimulants (MLE and PhytoStim®) also resulted in an increase in TPC, TTC and TPAC in M. peregrina, with a decline in total contents of these compounds in M. oleifera. However, the decline did not negatively impact both species' pharmacological abilities (antioxidant and antimicrobial activities), as they exhibited stronger antioxidant and antimicrobial activities when compared to the untreated plants (control samples). The use of the above mentioned plant based biostimulants resulted in an enhanced adaptability as indicated by the increase in the accumulation of selected screened secondary metabolites plant samples that exhibited signs of stress. The higher accumulation of secondary metabolites was observed under 600 ppm, in combination with PhytoStim® for either species. The combined CO2 and biostimulant treatments improved the total phenolic content (TPC) of both M. oleifera and M. peregrina significantly, with M. oleifera showing higher TPC content when compared to M. peregrina. On average, both M. oleifera and M. peregrina exhibited lower total flavonoid content (TFC), total tannin content (TTC) and total proanthocyanidins (TPAC), with M. oleifera showing higher contents of the above-mentioned phytochemicals in comparison to M. peregrina. The study also highlighted a decline in biological activities for all treatments, with the controls showing higher biological activities for both species. In the three antioxidant assays conducted, the leaf extracts of the controls had significant lower IC50 values for DPPH and H2O2, when compared to the stressed M. oleifera and M. peregrina. Antimicrobial assays also showed no significant difference in the bacterial inhibition capabilities of M. peregrina and M. oleifera under 600 ppm and 800 ppm with either biostimulant application. M. peregrina and M. oleifera controls showed high ZOI for the selected bacterium. The study has demostrated that biostimulants (MLE and PhytoStim®) enhanced the adaptability of both species under potential stress coursed by eCO2. The present study has demonstrated that the exposure to elevated CO2 could alter the accumulation and biological processes (such as antioxidant activity and antimicrobial activity) in both M. oleifera and M. peregrina. Moringa peregrina exhibited more tolerance to elevated CO2 when compared to Moringa oleifera and showed higher antioxidant and antimicrobial activity which might be attributed to the stronger presence of phytochemicals such as flavonoids, phenols and tannins. The data also suggests that both Moringa oleifera and M. peregrina can adapt to high levels of CO2 concentrations (~600 ppm), however, as medicinal plants, it might be difficult to sustain the acclimatisation and tolerance due to membrane oxidation and DNA damage. Therefore, foliar application of the biostimulants could enhance the adaptability and productivity of both species under high levels of CO2. This study may contribute towards better planning on conservation efforts to improve the chances of survival of the Moringa oleifera and M. peregrina and could aid with food security.
This dissertation is submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, at the School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Moringa; Biostimulant; Climate change; Antioxidant; Anti-bacteria; Secondary metabolites; Medicinal plants; Bioactivity; UCTD; SDG-3: Good health and well-being